The Latin and Ancient Greek Dependency Treebanks - Bamman, David; Crane, Gregory (Tufts Archival Research Center, 2005)
This paper describes the development, composition, and several uses of the Ancient Greek and Latin Dependency Treebanks, large collections of Classical texts in which the syntactic, morphological and lexical information for each word is made explicit. To date, over 200 individuals from around the world have collaborated to annotate over 350,000 words, including the entirety of Homers Iliad and Odyssey, Sophocles Ajax, all of the extant works of Hesiod and Aeschylus, and selections from Caesar, Cicero, Jerome, Ovid, Petronius, Propertius, Sallust and Vergil. While perhaps the most straightforward value of such an annotated corpus for Classical philology is the morphosyntactic searching it makes possible, it also enables a large number of downstream tasks as well, such as inducing the syntactic behavior of lexemes and automatically identifying similar passages between texts.